Gender-Based Differences in EFL Writing: Linguistic Features in Indonesian High School Students’ Narratives - Miftahur Ridha; T. Silvana Sinar, T. Silvana; Zein, T. Thyrhaya (Elsya : Journal of English Language Studies, 2024)
This study uniquely investigates gender-based differences in the linguistic features of narrative texts within the under-researched context of Indonesian high school students learning English as a Foreign Language (EFL). Focusing specifically on narrative writing, this research provides novel insights into how gender influences written expression. Using a qualitative content analysis approach, narrative texts were collected from 20 students (10 male and 10 female) enrolled in a tutoring and English course institution in Indonesia. The texts were analyzed to identify lexicogrammatical features, as outlined by Knapp (2005), with particular attention to the use of action and mental verbs. The findings revealed that male students predominantly used action verbs to describe challenging activities and responsibility, such as "fought against big waves," highlighting assertiveness and leadership traits. In contrast, female students employed more mental verbs, such as "felt happy and proud," emphasizing emotions and personal experiences, which reflected a more introspective and relational writing style. These findings highlight the alignment of gender-based differences with social norms and cultural expectations. The study suggests that using gender-sensitive methodologies in EFL teaching enhances inclusivity by addressing students’ diverse communication needs. This research makes a valuable contribution by proposing practical, gender-responsive strategies for language education.